Gender and social support for Singapore's aging population - Wong, Jertaime Xi Ting (2015)
The research study aims to find out gender differences among Singaporean aged persons, who are aged 62 years old and above, in the usage of social support sources. The study’s hypothesis is that the married Singaporean elderly persons’ social support preferences, formal or informal support, reflect the impact of gender roles. Formal support refers to government programmes and elderly care services provided by private and non-profit organisations while informal support refers to the aged person’s immediate/extended family members, neighbours and friends. Findings revealed that female elderly respondents preferred informal support while majority of the male elderly respondents were receptive towards formal support. Through the application of Max Weber’s (1956) Social Action Theory, this study argues that the elderly persons’ need to conform to “gendered expectations” (Wharton 2012:61) while leading an independent lifestyle, thus led them to prefer either formal or informal support.